2017
DOI: 10.1142/s0217751x17501469
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative Brownian motion

Abstract: We investigate the classical Brownian motion of a particle in a two-dimensional noncommutative (NC) space. Using the standard NC algebra embodied by the sympletic Weyl-Moyal formalism we find that noncommutativity induces a non-vanishing correlation between both coordinates at different times. The effect stands out as a signature of spatial noncommutativity and thus could offer a way to experimentally detect the phenomena. We further discuss some limiting scenarios and the trade-off between the scale imposed b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…the factorization theorem is conserved in both commutative and NC space). In the same idea, Santos et al [27] found that, NCty induces a non-vanishing correlation between both coordinates at different times. Very recently in our previous works on decoherence of quantum Brownian particle in NC space, we realized that the NCty effects intervene in the system as a disruption and therefore, increase the rate of decoherence in the system [28].…”
Section: Introductionmentioning
confidence: 90%
“…the factorization theorem is conserved in both commutative and NC space). In the same idea, Santos et al [27] found that, NCty induces a non-vanishing correlation between both coordinates at different times. Very recently in our previous works on decoherence of quantum Brownian particle in NC space, we realized that the NCty effects intervene in the system as a disruption and therefore, increase the rate of decoherence in the system [28].…”
Section: Introductionmentioning
confidence: 90%
“…Due to the extensive domain of quantum thermodynamics [50][51][52], an interesting fundamental question is how noncommutativity could modify thermodynamics protocols in quantum scales. Motivated by the same issue, noncommutativity has been addressed in some models of quantum heat machines [53][54][55] as well as in dissipative dynamics of Brownian particles [56,57] and Gaussian states [58]. In this work we address the question of how noncommutativity in phase-space could impact the heat flow between two interacting systems with different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that the topological order (mainly characterized by the quantized Hall conductance) of two-dimensional TI are generally degraded by the interaction with a bosonic thermal bath [24,25,26], though smarter characterizations of this new symmetry have recently indicated that the topological features can be resilient to moderate temperature effects [27]. Closely related works have also searched for observables signatures of spatial noncommutative effects in the conventional Brownian motion [21,28,29].…”
Section: Introductionmentioning
confidence: 99%